The Audacious Searching of Spanish Mothers: The Appropriation of Babies During and After the Dictatorship - Escudero, Carolina (Advances in Social Sciences Research Journal, 2022)
Throughout the dictatorship in Spain, many strategies were used to manipulate and silence mothers’ voices. During this period (1940-1975) and also in later times of democracy, a total of 300,000 babies were stolen (Anadir, 2011). Currently, family organizations are looking for their children, stolen between 1940 and 1999. Their calls for memory, justice and reparation found a space for action in social media as the campaigns “We Are Looking for You” (2017, 2018), where they could their search after surviving obstetric violence and stigmatization. Transcending these deeds from a space of action, the precepts proposed by Frankl –on accepting pain, taking responsibility for what they feel in order to give meaning to the tragedy– are observed. Through this ethnographic study, carried out during the recording of two social media campaigns, we will endeavor to confirm the following hypothesis: their active participation in the campaigns, the members of SOS Stolen Babies of Catalonia are developing the virtue of audacity. This audacity is linked to Frankl’s theory of assuming suffering, asserting destiny and taking a stand before it (1987). This study used participant observation and interviews of the 20 families belonging to the Catalan organization.